2017
DOI: 10.1527/tjsai.wii-d
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Exploratory Information Access Based on Comic Content Information

Abstract: SummaryThe purpose of this research is supporting information access based on the contents of comic books. To meet this purpose, it is necessary to obtain information related to the story and the characters of a comic. We propose a method to extract information from reviews on the Web by using term frequency-inversed document frequency (TF-IDF) method and hierarchical Latent Dirichlet Allocation (hLDA) method, which intends to solve the problem. By using these methods, we build a prototype system for explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…As mentioned above, in this research, we concluded that the named entity in the review sentence is information that can not be referred to for grasping the contents, and such part of speech is excluded from the analysis target in advance. However, it was confirmed that some named entities were classified as general nouns in the analysis results [9]. This is because the MeCab 5 morphological analysier was unable to analyze all the existing named entities during the comic review.…”
Section: Named Entity In Comic Reviewsmentioning
confidence: 92%
See 4 more Smart Citations
“…As mentioned above, in this research, we concluded that the named entity in the review sentence is information that can not be referred to for grasping the contents, and such part of speech is excluded from the analysis target in advance. However, it was confirmed that some named entities were classified as general nouns in the analysis results [9]. This is because the MeCab 5 morphological analysier was unable to analyze all the existing named entities during the comic review.…”
Section: Named Entity In Comic Reviewsmentioning
confidence: 92%
“…In our previous research, we employed "preferable title" as the input query to reduce the cost of query generation [9]. As mentioned in the previous section, query patterns that respond to content-related requests may vary.…”
Section: Supporting Information Access With Exploratory Searchmentioning
confidence: 99%
See 3 more Smart Citations